2006
DOI: 10.1308/003588406x98621
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Surgical Instruments

Abstract: This study demonstrates the value of local quality control for surgical instruments. This is of importance in an increasingly hazard-conscious environment, where there are concerns over instrument sterilisation, surgical glove puncture and the potential for transmission of blood-borne and prion diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 2 publications
0
12
0
1
Order By: Relevance
“…In the United Kingdom, Daly et al reported on a pilot study of a Surgical Instruments Service to assess the quality of instruments purchased by the hospital, remove those unfit for purpose, and inform the manufacturer [2]. Brophy et al found that 15% of surgical instruments examined by medical and mechanical engineers failed to meet the appropriate British Standards (BS) guidelines [3]. Instruments purchased from certain manufacturers failed at a rate of 35%, suggesting that potentially one in every three instruments in some sets are of substandard quality [4].…”
Section: Introductionmentioning
confidence: 99%
“…In the United Kingdom, Daly et al reported on a pilot study of a Surgical Instruments Service to assess the quality of instruments purchased by the hospital, remove those unfit for purpose, and inform the manufacturer [2]. Brophy et al found that 15% of surgical instruments examined by medical and mechanical engineers failed to meet the appropriate British Standards (BS) guidelines [3]. Instruments purchased from certain manufacturers failed at a rate of 35%, suggesting that potentially one in every three instruments in some sets are of substandard quality [4].…”
Section: Introductionmentioning
confidence: 99%
“…One risk reduction strategy was to ensure all surgical equipment was of highest possible quality. Quality control exercises highlight a strikingly high percentage of defective surgical instruments delivered to UK hospitals,26 and operating room incidents with potential to affect quality of care are most commonly equipment-related 27. Indeed, surgical environments are often busy and surgeons are rarely afforded time to optimise all possible variables prior to surgery, and even meticulous scrutiny will not eliminate risk.…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have suggested that the inferior quality of some surgical instruments may be a reflection of poor working conditions and low standards, particularly in the developing world. Responsibility lies with the suppliers from developed countries manufacturing in the developing world who behave in an unethical manner, maximising profits and minimising the remuneration of the people who actually produce the goods [ 9 - 11 ].…”
Section: Case Presentationmentioning
confidence: 99%